Masculinity In Spark’s The Best Me And Yanagihara’s A Little Life : A Study Of Comparative Literature - Alfiatin Niamah; Anita Rahmah Dewi (Institut Agama Islam Tarbiyatut Tholabah, 2023)
This study aims to explain the differences and similarities of masculinity depicted in the 17th American novel The Best of Me (2011) by Nicholas Sparks which is ranked 2 of the top 10 lists in weekly publishers, with romance and fiction genres, with Novel A Little Life (2015) the work of the United States novelist Hanya Yanagihara who won both the 2015 Man Booker Prize, the Goodreads choice awards for the best fiction category and the national book award for fiction. Using the fiction genre, this research is comparative literature. It uses gender theory with masculine concepts from John Beynon (2002) which is written in his book entitled Masculinities and Culture. This study uses a context-oriented approach,Data Collection Techniques using literature study by reading, taking notes, and documenting data. After the data is collected, data reduction is carried out. The data that has been selected will be classified to take action to analyze the differences and similarities of masculinity in the male main character Dawson Cole in the Novel The Best of Me with Jude in the Novel A Little Life. The author finds some differences in reading aspects of masculinity according to John Beynon in the two characters. The difference lies in aspects: Age & Physical, Education, Sexual Orientation, Class & Occupation, Status & Lifestyle. The author finds similarities in reading aspects of masculinity according to John Beynon in Dawson and Jude in the Historical Location aspect. Both of them have pasts that they dont not want to open up.